2010
DOI: 10.1002/jrs.2779
|View full text |Cite
|
Sign up to set email alerts
|

Self‐association and hydrogen bonding of propionaldehyde in binary mixtures with water and methanol investigated by concentration‐dependent polarized Raman study and DFT calculations

Abstract: The Raman spectra of neat propionaldehyde [CH 3 CH 2 CHO or propanal (Pr)] and its binary mixtures with hydrogen-donor solvents, water (W) and methanol (M), [CH 3 CH 2 CHO + H 2 O]and CH 3 CH 2 CHO + CH 3 OH] with different mole fractions of the reference system, Pr varying from 0.1 to 0.9 at a regular interval of 0.1, were recorded in the ν(C O) stretching region, 1600-1800 cm −1 . The isotropic parts of the Raman spectra were analyzed for both the cases. The wavenumber positions and line widths of the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In our earlier studies, [25][26][27][28][29][30] the combined Raman and DFT approach successfully has been applied to a large number of hydrogen-bonded systems, probing the intermolecular interactions and studying their influence on the spectral features. Raman spectra of Ade and its different complexes Ade-(Gly/Lys/Arg) at different molar ratios were recorded in the spectral region 1550-550 cm À1 .…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…In our earlier studies, [25][26][27][28][29][30] the combined Raman and DFT approach successfully has been applied to a large number of hydrogen-bonded systems, probing the intermolecular interactions and studying their influence on the spectral features. Raman spectra of Ade and its different complexes Ade-(Gly/Lys/Arg) at different molar ratios were recorded in the spectral region 1550-550 cm À1 .…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…17 There are a few quite early experimental studies, [18][19][20] which have dealt with structure determination of DMSO. Raman study of solutions of DMSO in carbon tetrachloride CCl 4 and water has been also reported, 21 for both parallel and perpendicular polarizations in the SLO stretching region. A few studies on the structure of the DMSO using different experimental techniques and in different environments were also carried out in the 909s.…”
Section: Introductionmentioning
confidence: 96%
“…As far as mixtures are concerned, experimental and simulation studies on aqueous liquid mixtures of organic molecules are frequent (see, e.g., Franks). On the other hand, investigations of alcohol/aldehyde mixtures are scarce: only a combined Raman spectroscopic and density functional theoretical (DFT) study of propionaldehyde/methanol, and a microwave dielectric relaxation investigation of n ‐propanol/propanal mixtures could be found.…”
Section: Introductionmentioning
confidence: 99%